Glucose and lipid levels with lanreotide autogel 120 mg in treatment‐naïve patients with acromegaly: data from the PRIMARYS study. (27th December 2016) - Caron, Philippe J.; Petersenn, Stephan; Houchard, Aude; Sert, Caroline; Bevan, John S.; ,
Summary: Objective: Impaired glycaemic control, characteristic of acromegaly, can be exacerbated by treatment with somatostatin analogues (SSAs), particularly those with multireceptor activity. We present data from the PRIMARYS study on the impact of the SSA lanreotide, associated with tumour volume and hormonal improvements, on glucose and other metabolic parameters in acromegaly. Design: PRIMARYS was a 48‐week open‐label single‐arm phase 3b study of lanreotide autogel 120 mg/4 weeks. A priori and post hoc metabolic profile data are reported for the overall population, patients with/without diabetes and patients achieving/not achieving hormonal control. Patients: Treatment‐naïve adults with pituitary macroadenoma, mean growth hormone >1 μg/l and elevated insulin‐like growth factor‐1 levels ( n = 90). Measurements: Glycaemic parameters [glycated haemoglobin (HbA1c ) and fasting plasma glucose (FPG) levels] assessed at baseline and weeks 12, 24 and 48. Lipid‐profile data (triglycerides, total cholesterol, high‐density lipoprotein cholesterol and low‐density lipoprotein cholesterol) collected at baseline and study end. Results: In patients with diabetes ( n = 24), HbA1c showed a clinically relevant decrease during treatment [mean change from baseline to week 48, −1·44% (95% CI: −2·52, −0·36)]. In the overall population, in patients without diabetes, or in patients with/without hormonal control, HbA1c did not significantly change by week 48. Mean FPG levels showed no significant change by week 48 in all populations. Individually, increases and decreases in glycaemic parameters affected some patients in all populations. Glycaemic status as a composite measure of HbA1c and FPG (classification as normal, mild or diabetic) was stable from baseline to study end in most patients (overall, 70%; patients with diabetes, 50%; patients without diabetes, 76%), but worsened by week 48 in nine (15%) patients [seven (50%) with diabetes at baseline] and improved in nine (15%) patients (none with diabetes). Changes in lipid profiles were not considered clinically meaningful. Conclusions: Glucose and lipid levels were not detrimentally affected in most patients, while only a relatively small proportion showed deterioration in glucose control.